Pemberdayaan Sosial Ekonomi Ibu Rumah Tangga melalui UMKM di Kelurahan Gunungpati - Hida Farhani Karismawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The involvement of housewives in the Micro, Small, and Medium Enterprises (MSME) sector is one of the strategic approaches to improving the socioeconomic conditions of families, especially in economically disadvantaged communities. This study aims to explore how the participation of housewives in MSMEs contributes to improving family welfare, identify the various challenges they face in running their businesses, and examine the role of local governments in supporting such empowerment programs. This study employs a qualitative descriptive method with data collection techniques including interviews, field observations, and documentation. The findings reveal that the involvement of housewives in MSMEs can increase household income and strengthen family economic independence. However, they also face challenges such as time constraints due to dual workloads, limited access to capital, and insufficient skills in digital marketing. The sub-district acts as an information hub through PKK cadres, facilitates collaboration with universities, and directs residents to participate in training programs from relevant government agencies. The conclusion of this study indicates that the empowerment process of housewives through MSMEs requires more intensive and sustainable cross-sectoral support to address the real challenges faced by the community and strengthen family economic resilience comprehensively.